Office 2013: Master of the Essentials: In Easy Steps - Price, Michael (New Delhi Mc-Graw Hill, 2013)
Office 2013 in easy steps will guide users through microsoft's latest version of office, so they will soon master its new features. This new release works with touch, stylus, mouse or keyboard across windows devices, including tablets. Sign in with a microsoft id and use the software across different platforms. Office 2013 in easy steps concentrates on the most useful and productive elements of office 2013, covering the basics of word, excel, outlook and powerpoint. It also introduces other office applications such as access, onenote, publisher, infopath designer & filter and lync. Aimed at both new and experienced users, office 2013 in easy steps covers the essential functions of ms office in easy steps.table of contents:introducing office 2013 create word documents complex documents calculations manage data presentations office extras email time management manage files and fonts up-to-date and secure where next? index
Includes Index and Illustrations.
Keywords: Office 2013